Antiinflammatory Activity of Aqueous Extract of Coccinia grandis L. Voigt Leaves and Stem - Deshpande, S.V.; Patil, M.J.; Daswadkar, S.C.; Suralkar, U.; Agarwal, A. (Asian Journal of Chemistry, 2011)
The aqueous extracts of leaves and stem of Coccinia grandis were investigated in chemicallyinduced inflammation rodents model. The aqueous extract of Coccinia grandis leaves (AEL) and stem (AES) were prepared and subjected to acute toxicity study as per CPCSEA guideline No. 423. The doses of 50, 100 and 200 mg/kg were selected for both leaves and stem extracts for further studies. The extracts inhibited carrageenan-induced paw edema in rats. These inhibitions were statistically significant (p < 0.001) as compared to control. Aqueous extract of leaves showed highest activity. The antiinflammatory activity of the extracts may be attributed to the reported polyphenolic, steroidal and flavonoid constituents of the plants.